(untitled) (Research, Society and Development, 2021)
Health Care Related Infections are multifactorial and occur due to factors that could be avoided, such as inadequate hand washing and material handling. The objective of this study was to know the bacteriological profile of the hands and cell phones of the multidisciplinary team and professionals who attend the Intensive Care Unit of the HU-UNIVASF. The hands and cell phones of the multidisciplinary ICU team were analyzed. The research was divided into 3 groups: group 1: dominant hand and/or cell phone of professionals who make up the multidisciplinary team who arrive at the sector for the duty; group 2: dominant hand and/or cell phone of professionals who make up the multidisciplinary team who leave the sector at the end of their shift and group 3: dominant hand and/or cell phone of professionals who enter the ICU to perform some activity. After passing the swab, in the hands and in cell phones, the samples were transported to the Laboratory where the microbiological analysis was performed. In the hands and cell devices, the incidence of the main bacteria causing infections can be observed, they are: Acinetobacter baumannii, Pseudomonas aeruginosa, Klebsiella pneumoniae, Enterococcus spp. and Staphylococcus aureus. Regarding the bacteriological profile, it is observed that the isolated bacteria have different resistance profiles, including the presence of multiresistant bacteria. Professionals working in the ICU of the HU-UNIVASF and those who come in to carry out activities have in their hands and cell devices multiresistant bacteria that cause hospital infections that may cause cross-infection.